2020
DOI: 10.1002/htj.21774
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport analysis for natural convection in a porous corrugated rhombic enclosure

Abstract: A numerical study of fluid flow and heat transfer, applying natural convection is carried out in a porous corrugated rhombic enclosure. A uniform heating source is applied from the bottom boundary wall while the inclined side walls are maintained to a constant cold temperature and the top corrugated wall is retained at insulated condition inside the enclosure. The heat transfer and flow features are presented for a wide spectrum of Rayleigh numbers (Ra), 104 ≤ Ra ≤ 106, and Darcy numbers (Da), 10−3 ≤ Da ≤ 10−2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore, it was extensively used in modern heat exchangers applicated in steam generation, condensation in power and cogeneration plants, chemical and agricultural products, automobile industry, etc. [44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. Hasanuzzamana et al 2007 [44], studied the natural convection in a square cavity having two V-wavy parallel vertical plates and two flat horizontal plates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it was extensively used in modern heat exchangers applicated in steam generation, condensation in power and cogeneration plants, chemical and agricultural products, automobile industry, etc. [44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. Hasanuzzamana et al 2007 [44], studied the natural convection in a square cavity having two V-wavy parallel vertical plates and two flat horizontal plates.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that increasing the undulations number and buoyancy ratio led to reducing the performance of heat and mass transfer rate. Dutta et al 2020 [57], studied the natural convection in a porous corrugated rhombic cavity. It was noticed that the heat transfer process was indicated by the interaction between Rayleigh number and Darcy number together with a number of undulations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They calculated the exact solution using separation of variables. More studies about fluids can be seen in References [8‐44].…”
Section: Introductionmentioning
confidence: 99%